How do external factors contribute to the hypocoagulative state in trauma-induced coagulopathy? – In vitro analysis of the lethal triad in trauma - Michael Caspers; Nadine Schäfer; Matthias Fröhlich; Ursula Bauerfeind; Bertil Bouillon; Manuel Mutschler; Marc Maegele (Scandinavian Journal of Trauma, Resuscitation and Emergency Medicine, 2018)
Abstract Background External factors following trauma and iatrogenic intervention influence blood coagulation and particularly clot formation. In particular, three external factors (in detail dilution via uncritical volume replacement, acidosis and hypothermia), in combination, referred to as the “lethal triad”, substantially aggravate the hypocoagulative state after trauma. Contribution of these external factors to the resulting hypocoagulative state in trauma and especially their influence on primary haemostasis has still not been investigated systematically. This study aims to assess this contribution to the aggravating hypocoagulative state in trauma-induced coagulopathy (TIC) using an in vitro simulation assay. Emphasis is given to platelet contribution to clot formation and to the investigation of how platelet activation alters under the respective conditions. Methods To simulate the conditions of lethal triad in vitro, whole blood samples taken from five healthy volunteers were introduced to the respective conditions. Besides standard coagulation testing, thrombelastometric analysis and differentiated platelet mapping were performed. Results All three simulated conditions induced significant impairments of clot formation (clot formation time, CFT; α -angle) and propagation (maximum clot firmness, MCF; Diameter A5-A25), with the highest impact under hypothermia and dilution. Consistently, lethal triad resulted in an additive effect of all conditions. None of the simulated conditions induced a statistically relevant change in coagulation initiation assessed by EXTEM and FIBTEM thrombelastometry. Platelet contribution to clot formation decreased gradually under the respective conditions, reaching statistical significance for simulated dilution, and attaining its greatest extent under the conditions of lethal triad (Δtrias/baseline 0.59; p = 0.01). Consistent, reduced CD62 expression levels were observed under experimental acidosis (Δacidosis/baseline 0.32; p = 0.006), dilution (Δdilution/baseline 0.34; p = 0.01) and lethal triad (Δlethal triad/baseline 0.24; p = 0.01). Conclusion The respective external factors of lethal triad play a pivotal role in the development of coagulopathy, essentially influencing the kinetics of clot formation, and to a varying extent clot diameter, as measured by thrombelastometry. Moreover, impairment of platelet function under the conditions of lethal triad plays a key role in the pathophysiology of TIC, resulting in reduced responsiveness to stimulation with ADP that might also be present after trauma. Our data indicate that impairment of primary haemostasis contribute to the hypocoagulative state in TIC after trauma aggravated by external factors of lethal triad.